THE IMPACTS OF PERFORMANCE FUNDING ON THE FACULTY EXPERIENCE: VIEWING FACULTY AS STREET-LEVEL BUREAUCRATS OR PASSIVE RECIPIENTS - Jenkins, Brandon M (East Carolina University, 2020)
This comparative case study examined how performance funding programs shape the faculty experiences at two North Carolina Community Colleges. Using Principal-Agent Theory, Street-Level Bureaucracy, and Bottom-Up Policy Perspective as theoretical frameworks, six themes and four subthemes emerged from semi-structured interviews of twenty community college faculty members. The study revealed that (1) faculty experiences are shaped according to the institutions' overall capacity and response to performance funding; (2) the awareness of faculty regarding performance funding is dependent upon the institutions' efforts to share information; and (3) depending upon the institution, faculty can be seen as both street-level bureaucrats and passive recipients of performance funding initiatives. While performance funding programs can result in the Principal-Agent dynamic, Bottom-Up Policy Perspective, and street-level bureaucracy, each of these is dependent upon the sharing of information. Institutional efforts to improve performance often negate the demands on faculty time and fail to include faculty in decision making processes. Furthermore, institutional budget concerns take precedence and create greater problems than those of performance funding. Finally, key practical implications for community colleges and educational systems are that (1) information regarding performance funding and any subsequent budgetary allotments should be readily available to all faculty; (2) institutional initiatives and response mechanisms aimed at improving performance should be inclusive of the entire faculty body; (3) significant attention should be given to the conditions that lead to the weakening of academic standards; and (4) educational systems should examine performance funding systems while weighing the capability of all institutions to effectively respond.
Keywords: North Carolina Community College System; Community college teachers--North Carolina